KINERJA PEGAWAI MELALUI PILAR PEMBANGUNAN AKHLAK DAN MORAL - Yanti, Adri (Jurnal Ilmu Administrasi Negara, 2016)
Employee Performance Through the Pillars of Virtue and Moral Development. This study aims to determine employee performance through the development of character and moral pillar in service revenue, finance and asset management Kampar district, as well as determine the factors that influence on employee performance. Data collected through interviews with informants consisting of kapala section, subsection all parts,. Analysis of data is supported by the observation and documentation relating to the problems examined. The results showed that the performance of employees through the development pillars of character and morals at the Department of Revenue, Finance and Asset Management Kampar regency has not been so good. However, the impact of the policy pillars of development of moral character and has been able to improve employee work discipline in the implementation of the tasks and responsibilities of each.